RETELLING SHORT STORY TO IMPROVE STUDENTS’ SPEAKING SKILL - Novia, Jessica (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study is aimed to investigate whether or not the use of retelling short story improves the students’ speaking skill and to find out the effect size of the improvement of students’ speaking skill after being taught using retelling short story of the tenth grade students of SMA Santun Untan Pontianak. The form of this research is pre-experimental study with one group pre-test post-test design. The population of this research is the tenth grade students of SMA Santun Untan Pontianak, while the sample is class X B that consists of 24 students. The research findings show that the mean score of pre-test is 56,04 while the mean score of post-test is 61,46. It shows that retelling short story improves the students’ speaking skill.The result of the research shows that t-test is higher than t-critical the value is 8,34>2.069 it means that  the alternative hypothesis (Ha) is accepted. It can be concluded that there is a highly significant effect of retelling short story to improve students’ speaking skill on the tenth grade students of SMA Santun Untan Pontianak. Keywords: Retelling Short Story, Speaking Skill